Macrozoobenthos Diversity in The Fisheries Mangrove Ecotourism Area in Pulau Banyak Village Langkat District - Manullang, Helentina Mariance; Lubis, Zulkarnain; Sabrina, Raja (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Mangroves are important ecosystems located in tidal areas and become habitats for various types of biota, including macrozobenthos. Macrozobenthos is a group of animals that inhabit the bottom waters of mangrove ecosystems. This study aims to analyze the diversity of macrozobenthos species in the mangrove ecotourism area of Pulau Banyak village, Langkat Regency, North Sumatra. This research was conducted from October 2022 to October 2023 in the fisheries-based mangrove ecotourism area in Pulau Bayak village, Langkat Regency. The research location was divided into three research stations. Macrozobentos observations were made once a month. Sample collection is done by collecting directly by hand, the samples collected are on the sample map (plot) measuring 1 x 1 meter making as many as 10 pieces for every 100 m2. Data were analyzed using the Paleontological Statistic (PAST) Version 4.0 tool. Parameters studied include diversity index, evenness, species richness, and dominance. Based on the results of the analysis, it is known that the diversity index is in the medium category with a value of 2.4-2.5, while the evenness index is in the high category with a value of 0.91 - 0.92, then the species richness index is in a low category with a value of 2.20 - 2.22 and the dominance index shows that there are no certain species that dominate this ecosystem with an index value close to 0. Thus, it can be concluded that this fisheries-based mangrove ecotourism area is in good condition and can support the lives of organisations associated with mangrove ecosystems.